2015
DOI: 10.4236/ojms.2015.52018
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Marine Pollution on Nigerian Coastal Resources: An Overview

Abstract: Little is known about the full impacts of marine litter, especially in the open ocean where there is almost no information. The ocean is a vital source of nourishment, especially to the people in the world's poorest nations. Many depend on fish for their source of protein; fisheries and aquaculture support the livelihoods of about 540 million people directly or indirectly [1]. Overfishing, loss of biodiversity and possible extinction of species put stress on these limited resources. Some beaches are already cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This result corroborates that of Kadafa (2012) who in his study reported a mean age of 40 years among fishermen in Niger Delta Region. It also corroborates those of Akankali and Elenwo, (2015) reported a mean age of 41 years in their study of sources of marine pollution on Nigerian coastal resources in the Niger Delta region of Nigeria. The table further showed that majority (57.0%) of the respondents was married, 20.5% were single, 15.0% were divorced while 7.5% were widow/widower.…”
Section: Results and Discussion 41 Socioeconomic Characteristics Of R...supporting
confidence: 90%
See 1 more Smart Citation
“…This result corroborates that of Kadafa (2012) who in his study reported a mean age of 40 years among fishermen in Niger Delta Region. It also corroborates those of Akankali and Elenwo, (2015) reported a mean age of 41 years in their study of sources of marine pollution on Nigerian coastal resources in the Niger Delta region of Nigeria. The table further showed that majority (57.0%) of the respondents was married, 20.5% were single, 15.0% were divorced while 7.5% were widow/widower.…”
Section: Results and Discussion 41 Socioeconomic Characteristics Of R...supporting
confidence: 90%
“…These findings corroborated those of Aniefiok et al (2018) who reported that oil spillage reduced fishermen's income, increase food insecurity and reduce quantity of catch. Similarly, Akankali and Elenwo, (2015) also listed pollution of environment and resulting in youth restiveness as possible causes of oil spillage.…”
Section: 3: Effects Of Oil Spillage On Socioeconomic Wellbeing Of Art...mentioning
confidence: 99%